Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/path.4841
|View full text |Cite
|
Sign up to set email alerts
|

Functional and prognostic significance of the genomic amplification of frizzled 6 (FZD6) in breast cancer

Abstract: Frizzled receptors mediate Wnt ligand signalling, which is crucially involved in regulating tissue development and differentiation, and is often deregulated in cancer. In this study, we found that the gene encoding the Wnt receptor frizzled 6 (FZD6) is frequently amplified in breast cancer, with an increased incidence in the triple‐negative breast cancer (TNBC) subtype. Ablation of FZD6 expression in mammary cancer cell lines: (1) inhibited motility and invasion; (2) induced a more symmetrical shape of organoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 50 publications
2
63
0
Order By: Relevance
“…We identified 448 differentially methylated genes (corresponding to 1269 probes) seem to have a role during early invasion represented by the Clark staging system (Table ). Of note, 18 out of the 385 genes in our data set show overlap with the TCGA data, of which several genes ( MECOM , CHD5 , TRIM55 , FZD6 , TPBG and TRPC4 ) were observed in association with invasion …”
Section: Resultsmentioning
confidence: 77%
“…We identified 448 differentially methylated genes (corresponding to 1269 probes) seem to have a role during early invasion represented by the Clark staging system (Table ). Of note, 18 out of the 385 genes in our data set show overlap with the TCGA data, of which several genes ( MECOM , CHD5 , TRIM55 , FZD6 , TPBG and TRPC4 ) were observed in association with invasion …”
Section: Resultsmentioning
confidence: 77%
“…Wnt5a/5b and ROR1 are involved in breast cancer invasiveness and metastasis independent of β‐catenin signaling . FZD6 promotes TNBC cell motility and distant metastasis through the fibronectin‐actin axis . These studies indicate that noncanonical Wnt signaling is involved in basal‐like breast cancer/TNBC progression.…”
Section: Wnt Signaling Is Overactivated In Basal‐like Breast Cancer/tnbcmentioning
confidence: 76%
“…Earlier studies have demonstrated the involvement of several Frizzled receptors, including FZD8, FZD2, FZD3, FZD4, FZD5, FZD6, FZD7, and FZD10 in different cancers. Though Frizzled receptors function as key components of the Wnt signaling pathway, the specific link with the ETS‐related transcription factor ERG is unknown.…”
Section: Discussionmentioning
confidence: 99%